A Matter of Trust: Online Proctored Exams and the Integration of Technologies of Assessment in Medical Education. Issue 4 (8th August 2022) - Fawns, Tim; Schaepkens, Sven
Abstract: Issue: Technology is pervasive in medicine, but we too rarely examine how it shapes assessment, learning, knowledge, and performance. Cultures of assessment also shape identities, social relations, and the knowledge and behavior recognized as legitimate by a profession. Therefore, the combination of technology and assessment within medical education is worthy of review. Online proctoring services have become more prevalent during the Covid-19 pandemic, as a means of continuing high-stakes invigilated examinations online. With criticisms about increased surveillance, discrimination, and the outsourcing of control to commercial vendors, is this simply "moving exams online", or are there more serious implications? What can this extreme example tell us about how our technologies of assessment influence relationships between trainees and medical education institutions? Evidence: We combine postdigital and postphenomenology approaches to analyze the written component of the 2020 online proctored United Kingdom Royal College of Physicians (MRCP) membership exam. We examine the scripts, norms, and trust relations produced through this example of online proctoring, and then locate them in historical and economic contexts. We find that the proctoring service projects a false objectivity that is undermined by the tight script with which examinees must comply in an intensified norm of surveillance, and by the interpretation of digital data by unseen human proctors. Nonetheless, such proctoring services are promoted by an image of data-driven innovation, a rhetoric of necessity in response to a growing problem of online cheating, and an aversion, within medical education institutions, to changing assessment formats (and thus the need to accept different forms of knowledge as legitimate). Implications: The use of online proctoring technology by medical education institutions intensifies established norms, already present within examinations, of surveillance and distrust. Moreover, it exacerbates tensions between conflicting agendas of commercialization, accountability, and the education of trustworthy professionals. Our analysis provides an example of why it is important to stop and consider the holistic implications of introducing technological "solutions", and to interrogate the intersection of technology and assessment practices in relation to the wider goals of medical education.